Development of a continuous process for α-thio-β-chloroacrylamide synthesis with enhanced control of a cascade transformation - Dennehy, Olga C.; Cacheux, Valérie M. Y.; Deadman, Benjamin J.; Lynch, Denis; Collins, Stuart G.; Moynihan, Humphrey A.; Maguire, Anita R. (Beilstein Journal of Organic Chemistry, 2016)
A continuous process strategy has been developed for the preparation of α-thio-β-chloroacrylamides, a class of highly versatile synthetic intermediates. Flow platforms to generate the α-chloroamide and α-thioamide precursors were successfully adopted, progressing from the previously employed batch chemistry, and in both instances afford a readily scalable methodology. The implementation of the key α-thio-β-chloroacrylamide casade as a continuous flow reaction on a multi-gram scale is described, while the tuneable nature of the cascade, facilitated by continuous processing, is highlighted by selective generation of established intermediates and byproducts.
Keywords: α-thio-β-chloroacrylamides; cascade reactions; flow chemistry

(untitled) - Murphy, M.; Lynch, D.; Schaeffer, M.; Kissane, M.; Chopra, J.; O’Brien, E.; Ford, A.; Ferguson, G.; Maguire, A. R. (Org. Biomol. Chem., 2007)

(untitled) - Maguire, A. R.; Murphy, M. E.; Schaeffer, M.; Ferguson, G. (Tetrahedron Lett., 1995)

(untitled) - Kissane, M.; Maguire, A. R. (Synlett, 2011)

(untitled) - Kissane, M.; Murphy, M.; O’Brien, E.; Chopra, J.; Murphy, L.; Collins, S. G.; Lawrence, S. E.; Maguire, A. R. (Org. Biomol. Chem., 2011)

(untitled) - Kissane, M.; Lynch, D.; Chopra, J.; Lawrence, S. E.; Maguire, A. R. (Org. Biomol. Chem., 2010)

(untitled) - Kissane, M.; Murphy, M.; Lynch, D.; Ford, A.; Maguire, A. R. (Tetrahedron, 2008)

(untitled) - Kissane, M.; Lawrence, S. E.; Maguire, A. R. (Org. Biomol. Chem., 2010)

(untitled) - Kissane, M.; Maguire, A. R. (Chem. Soc. Rev., 2010)

(untitled) - Kissane, M.; Lawrence, S. E.; Maguire, A. R. (Tetrahedron, 2010)

(untitled) - Kissane, M.; Lynch, D.; Chopra, J.; Lawrence, S. E.; Maguire, A. R. (Tetrahedron: Asymmetry, 2008)

(untitled) - Kissane, M.; Lawrence, S. E.; Maguire, A. R. (Tetrahedron: Asymmetry, 2010)

(untitled) - Kissane, M.; Murphy, M.; Lawrence, S. E.; Maguire, A. R. (Tetrahedron: Asymmetry, 2010)

(untitled) - Tietze, L. F. (Chem. Rev., 1996)

(untitled) - Wegner, J.; Ceylan, S.; Kirschning, A. (Adv. Synth. Catal., 2012)

Microreactors in Organic Chemistry and Catalysis - Wirth, T. (Wiley-VCH Verlag GmbH & Co. KGaA, 2013)

(untitled) - Baxendale, I. R.; Brocken, L.; Mallia, C. J. (Green Process. Synth., 2013)

(untitled) - Pastre, J. C.; Browne, D. L.; Ley, S. V. (Chem. Soc. Rev., 2013)

(untitled) - Webb, D.; Jamison, T. F. (Chem. Sci., 2010)

(untitled) - McQuade, D. T.; Seeberger, P. H. (J. Org. Chem., 2013)

(untitled) - Hartman, R. L.; McMullen, J. P.; Jensen, K. F. (Angew. Chem., Int. Ed., 2011)

(untitled) - Gutmann, B.; Cantillo, D.; Kappe, C. O. (Angew. Chem., Int. Ed., 2015)

(untitled) - Movsisyan, M.; Delbeke, E. I. P.; Berton, J. K. E. T.; Battilocchio, C.; Ley, S. V.; Stevens, C. V. (Chem. Soc. Rev., 2016)

(untitled) - Deadman, B. J.; Collins, S. G.; Maguire, A. R. (Chem. – Eur. J., 2015)

(untitled) - Müller, S. T. R.; Wirth, T. (ChemSusChem, 2015)

(untitled) - Deadman, B. J.; O’Mahony, R. M.; Lynch, D.; Crowley, D. C.; Collins, S. G.; Maguire, A. R. (Org. Biomol. Chem., 2016)

(untitled) - Kopach, M. E.; Roberts, D. J.; Johnson, M. D.; McClary Groh, J.; Adler, J. J.; Schafer, J. P.; Kobierski, M. E.; Trankle, W. G. (Green Chem., 2012)

(untitled) - Prat, D.; Wells, A.; Hayler, J.; Sneddon, H.; McElroy, C. R.; Abou-Shehada, S.; Dunn, P. J. (Green Chem., 2016)

(untitled) - Pinho, S. P.; Macedo, E. A. (J. Chem. Eng. Data, 2005)

(untitled) - Foley, D. A.; Doecke, C. W.; Buser, J. Y.; Merritt, J. M.; Murphy, L.; Kissane, M.; Collins, S. G.; Maguire, A. R.; Kaerner, A. (J. Org. Chem., 2011)